A Survey of Common Practices in Shell Egg Processing Facilities and Water Use - Jones, D.R.; Northcutt, J.K. (International Journal of Poultry Science, 2005)
Shell egg processing facilities in the U. S. were surveyed for common production practices and water use. Results were compiled and analyzed for frequency and significance via chi-square analysis. Of the respondents, 65.8 % utilized wells as their primary source of water. Furthermore, 19.2 % of the facilities discharged water to city sewers. Over half of the facilities processed 7 d each week with 8 to 9 h shifts (P < 0.05). There was a similar distribution of in-line, off-line and mixed operations represented in the responses. Two-thirds of the operations were dual washer systems with about half being plumbed separately. Over 90 % of the operations performed daily sanitation. Most facilities did not attempt to recycle water from their process. Fifty percent of the respondents utilized processing lines that are 5-15 yr old. The age of the processing line, number of processing days each week, size of facility and type of operation did not have a significant effect on water use.